Nomogram-based prediction of the risk of AVF maturation: a retrospective study - Zhao, Bin; Wang, Hui; Wang, Yuzhu; Zhan, Shen; Yu, Pei (Frontiers in Medicine, 2024)
Objective Early identification of autogenous arteriovenous fistula (AVF) maturation failure in patients with end-stage renal disease (ESRD) is crucial, as it enables early interventions that can enhance AVF maturation rates and reduce the duration of catheter use. This study aimed to identify factors that may predict arteriovenous fistula maturation in patients undergoing maintenance hemodialysis. Methods This retrospective study included a cohort of 532 ESRD patients who underwent AVF creation and routine follow-up at the Beijing Haidian Hospital (Haidian Section of Pecking University Third Hospital) from August 2018 to March 2022. A total of 532 patients were randomly divided into a training cohort (389 cases) and a validation cohort (143 cases). Patients in each cohort were categorized into mature and non-mature groups based on whether they met clinical or ultrasound criteria 3 months after AVF creation. The timing of early intervention for non-maturation AVF was preliminarily discussed after a risk prediction nomogram for non-maturation in newly AVF creation was constructed. Results Of the 532 patients, 379 (73.24%) achieved fistula maturation at 3 months postoperatively. We randomly divided the total study population using computer-generated randomization into a training cohort (n = 389) and a validation cohort (n = 143) in an approximately 7:3 ratio. Analysis of the training cohort revealed that the anastomotic diameter (anas1), the internal diameter of the anastomotic vein (V1), brachial artery blood flow (F1) at 1 month, and brachial artery blood flow (F3) at 3 months postoperatively were associated with AVF maturation. A maturation nomogram was developed for the training cohort, yielding an area under the curve (AUC) of 0.938 (95% confidence interval [CI], 0.908–0.967), with a sensitivity of 0.911 and a specificity of 0.856. The model was validated in the validation cohort, showing an AUC of 0.927 (95% CI, 0.879–0.975), with a sensitivity of 0.870 and specificity of 0.886. The calibration curve showed strong agreement between nomogram predictions and actual observations. Conclusion The anastomotic diameter (anas1), the internal diameter of the anastomotic vein (V1), brachial artery blood flow (F1) at 1 month, and brachial artery blood flow (F3) at 3 months postoperatively can predict the unassisted maturation of AVF.